(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to know the effect of the Woods model on acquiring scientific concepts for fifth-grade students in the bioscience of physics and their inferential thinking, as the two-group experimental curriculum was adopted, and the total sample of the experiment was (57) students from the fifth-grade scientific science in a school Within the General Directorate of Diyala Education for the academic year (2018-2019), as the sample was divided into two experimental groups, consisting of (29) students, which were studied using the Woods model and control of (28) students, which were studied in the usual way, and the equivalence of the two research groups was done in some variables that It’s possible To have an effect on the independent variable (Otis measure of mental ability, students’ chronological age in months, test their previous knowledge), and the educational material in question has been identified in chapters (1,2,3,4,5) for the book of physics for the fifth year of biomedical science and formulated Behavioral purposes The number reached (110). With regard to the tools used for research, a test was constructed for the acquisition of scientific concepts consisting of (36) objective paragraphs of the multiple choice type and then calculating the psychometric properties of it, and finding consistency for this test with the Koder Richardson formula 20 as it reached (0) 81) As for the second tool, it was represented by the scale of the instrument The reasoning reasoning adopted by the researcher for (Sabri, 2002), which consists of (35) paragraphs of the multiple choice type, and its validity was verified by adopting apparent honesty, logical honesty, and construction sincerity, and its validity was found by way of re-testing, as its stability factor reached 0,82). The completion of the experiment applied both the acquisition of scientific concepts and the inferential thinking scale to the two research groups and after analyzing the results statistically using the T-test for two independent samples of equal number, the results exceeded the experimental group that was studied according to the Woods model over the control group that studied According to the usual method The results indicated rejection of the first hypotheses Elsafreeten second and in the light that was out a number of conclusions and recommendations and proposals